A new species, Bulbophyllum phanquyetii and a new national record of B. tianguii (Orchidaceae) from the limestone area of northern Vietnam - Dang, Minh Quan; Averyanov, Leonid V.; Dang, van Son; Maisak, Tatiana; Bui, van Huong; Tu, Bao Ngan; Nguyen, van Canh; Truong, Ba Vuong (Phytotaxa, 2022)
Bulbophyllum phanquyetii, from Lai Chau Province was found and described as a new species for science. The new species looks similar to B. guttulatum and B. umbellatum but differs in the connate upper margin of lateral sepals, verruculose sepals and petals, and triangular stelidia. In addition, B. tianguii found in Ha Giang Province is firstly recorded for the orchid flora of Vietnam.